Dialysis dose and mortality in haemodialysis: is higher better?. Issue 12 (17th June 2021) - Béguin, Lisa; Krummel, Thierry; Longlune, Nathalie; Galland, Roula; Couchoud, Cécile; Hannedouche, Thierry
Abstract: Background: The effect of dialysis dose on mortality remains unsettled. Current guidelines recommend targeting a single-pool Kt/V (sp Kt/V ) at 1.20–1.40 per thrice-weekly dialysis session. However, the optimal dialysis dose remains mostly disputed. Methods: In a nationwide registry of all incident patients receiving thrice-weekly haemodialysis, 32 283 patients had available data on dialysis dose, estimated by Kt / V and its variants epuration volume per session ( Kt ) and Kt indexed to body surface area ( Kt / A ). Survival was analysed with a multivariate Cox model and a concurrent risk model accounting for renal transplantation. A predictive model of Kt in the upper quartile was developed. Results: Regardless of the indicator, a higher dose of dialysis was consistently associated with better survival. The survival differential of Kt was the most discriminating, but marginally, compared with the survival differential according to Kt / V and Kt / A . Patient survival was higher in the upper quartile of Kt (>69 L/session) then deteriorated as the Kt decreased, with a difference in survival between the upper and lower quartile of 23.6% at 5 years. Survival differences across Kt distribution were similar after accounting for kidney transplantation as a competing risk. Predictive factors for Kt in the upper quartile were arteriovenous fistula versus catheters and graft, haemodiafiltration versus haemodialysis, scheduled dialysis start versus emergency start, long weekly dialysis duration and sp Kt / V measurement versus double-pool equilibrated Kt / V . Conclusions: Our data confirm the existence of a relationship between dialysis dose and survival that persisted despite correcting for known confounders. A model for predicting a high dose of dialysis is proposed with practical relevance. Graphical Abstract: